Numerical algorithm for integrals with rapid oscilatory functions - Čiegis, Raimondas; Šablinskas, Ramūnas (Lietuvos matematikos rinkinys, 1999)
In this paper we consider numerical integration of rapid oscilatory functions for the laser beam diffraction field calculation problem. Two different methods are proposed and the accuracy of approximations are investigated. Numerical experiments are presented and analysed.